2017
DOI: 10.1007/s13671-017-0178-5
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Skin and Gut Microbiome in Psoriatic Disease

Abstract: Purpose To understand the changes in the microbiome in psoriatic disease, we conducted a systematic review of studies comparing the skin and gut microbiota in psoriatic individuals and healthy controls. Findings Our review of studies pertaining to the cutaneous microbiome showed a trend towards an increased relative abundance of Streptococcus and a decreased level of Propionibacterium in psoriasis patients compared to controls. In the gut microbiome, the ratio of Firmicutes and Bacteroidetes was perturbed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(101 citation statements)
references
References 72 publications
3
85
0
5
Order By: Relevance
“…The data presented in this preliminary study suggest a possible relationship between psoriasis, microbiome, gut barrier and immune system. A growing number of evidence emphasizes the role of skin and gut microbiota in psoriasis . Changes in microbiota have potent effects on gut permeability .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data presented in this preliminary study suggest a possible relationship between psoriasis, microbiome, gut barrier and immune system. A growing number of evidence emphasizes the role of skin and gut microbiota in psoriasis . Changes in microbiota have potent effects on gut permeability .…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal barrier disruption, along with genetic background and environmental factors, has been recently considered as a pivotal element in the pathogenesis of chronic inflammatory diseases, including inflammatory bowel disease and celiac disease . Recent experimental and clinical studies revealed disturbance in the balance of beneficial and pathogenic bacteria in the gut of patients with psoriasis and psoriatic arthritis . However, it remains unclear whether alteration in the gut microbiome and inflammatory processes in psoriasis influence the intestinal barrier.…”
Section: Introductionmentioning
confidence: 99%
“…For example, isogarcinol extracted from Garcinia mangostana L. inhibits inflammatory factors in LPS‐stimulated HaCaT cells and ameliorates IMQ‐induced psoriasis‐like skin lesions in mice . There has also recently been increased scientific interest in microbial contributions to healthy skin and cutaneous disorders . Furthermore, metabolomics has been used to study the local and systemic metabolic changes in psoriasis and has revealed novel insights into its pathogenesis and suggested new biochemical signatures .…”
Section: Discussionmentioning
confidence: 99%
“…Though studies of the skin microbiome, mycobiome, and virome in psoriatic disease are numerous (reviewed in Yan et al [47]), few studies have specifically focused on the gut microbes. Scher et al [48] compared the gut community composition in 16 psoriatic arthritis patients, 15 patients with psoriasis of the skin and 17 healthy matched controls.…”
Section: Psoriasis and Psoriatic Arthritismentioning
confidence: 99%